From information to public preparedness in the Cascadia Subduction Zone: Examining risk communication outcomes in Metropolitan Portland, OR. Issue 2 (May 2022) - MacPherson-Krutsky, Carson C; Brand, Brittany D; Lindell, Michael K
A Cascadia Subduction Zone (CSZ) earthquake will cause widespread damage along the Pacific Northwest (PNW) coast of the United States. It is, therefore, crucial to understand how to reduce future impacts across this region and assess current levels of household preparedness. Here, we examine whether decades of risk and preparedness campaigns have established protective knowledge and promoted hazard adjustments for residents of the Portland, Oregon metropolitan (PDX) region, an area where risk and preparedness campaigns have been increasing over the last decade. We also explore how PDX preparedness levels compare to those in other PNW regions using analogous data from multiple surveys over a 20-year time interval and assess PDX respondent's perceptions of risk information sources. We find that 63% of PDX residents do not intend to "Drop, Cover, and Hold On" (DCHO) when earthquake shaking starts and that, although residents are generally aware of earthquake hazards in the area, they are less aware of the specific risks for their homes. Furthermore, PDX residents' preparedness levels seem to be comparable to those recently surveyed in Washington, but somewhat less than those surveyed two decades ago in California, though more comprehensive data are needed to verify these results. We also find that people rate risk information provided by emergency managers and their websites as more accurate, understandable, relevant, and new than other sources. Our results suggest that significant gaps remain in translating broad awareness of the CSZ earthquake into personal knowledge and preparedness. This work provides guidance to PDX emergency educators for more targeted messaging and provides methods to measure preparedness variables in other regions for future comparisons. By paying close attention to preparedness gaps, local officials can use their limited resources more effectively to develop strategies to inform their communities and improve preparedness before a major earthquake strikes.